Journeys Towards Intercultural Capability in Language Classrooms Voices from Students, Teachers and Researchers - East, Martin (Intercultural Communication and Language Education, 2022)
This open access book presents an account of five teacher educators who, over a two-year period, undertook a research project with five teachers of languages other than English in pre-secondary schools in New Zealand. Their collaborative aim was to develop students' intercultural capability in the context of learning a new language. The school participants were typical of many in New Zealand's pre-secondary sector; the teachers had limited language-teaching experience and limited prior knowledge of how to develop the intercultural dimension in their language classrooms, and the students were largely at the beginning stages of learning a new language. The book discusses the findings obtained using a range of data collection methods, including classroom observations, reflective interviews with teachers, and focus groups with students. It documents instances of breakthrough and growth for teachers and students and reveals the problems and tensions. Lastly, it reflects on the lessons learned in the course of this project and speculates on the roles that teacher education needs to play if the goal of intercultural capability is to be better achieved in language classrooms, both in New Zealand and internationally. Of interest to a wide range of stakeholders in the area of education, the book allows readers to gain an understanding of the opportunities of working with teachers through an action-research model, alongside the challenges that this brings and ways in which intercultural capability may be strengthened.